Prognostic Significance of Altered ATRX/DAXX Gene in Pancreatic Neuroendocrine Tumors: A Meta-Analysis - Wang, Fei; Xu, Xiaowu; Ye, Zeng; Qin, Yi; Yu, Xianjun; Ji, Shunrong (Frontiers in Endocrinology, 2021)
Background: Pancreatic neuroendocrine tumors (PanNETs) are a heterogeneous group of neoplasms with increasing incidence and unpredictable behavior. Whole-exome sequencing recently has shown very frequent somatic mutations in the alpha -thalassemia/mental retardation X-linked (ATRX) and death domain-associated protein (DAXX) genes in PanNETs. And the prognostic significance of altered ATRX/DAXX genes in PanNETs patients have been revealed in several reports. However, many of these include small sample size and hold controversial opinions. To increase statistical power and, we performed a systematic review and meta-analysis to determine a pooled conclusion. We examined the impact of altered DAXX/ATRX genes mainly on overall survival (OS) and disease-free survival (DFS) in PanNETs. Methods: Eligible studies were identified and quality was assessed using multiple search strategies (last search February 2021). Data were collected from studies about prognostic significance of altered ATRX/DAXX in PanNETs. Studies were pooled, and combined hazard ratios (HRs) with 95% confidence intervals (CIs) were used to estimate strength of the associations. Results: Thirteen studies involving 1752 patients treated for PanNETs were included. After evaluating for publication bias, disease-free survival was significantly shortened in patients with altered ATRX/DAXX gene, with a combined HR 5.05 (95% confidence interval (CI): 1.58-16.20, P = 0.01). However, the combined data showed there were no difference between patients with altered ATRX/DAXX gene or not in overall survival, with a combined HR 0.71 (95% confidence interval (CI): 0.44-1.15, P = 0.23). We also performed a subgroup analysis with metastatic patients in overall survival, showing a combined HR 0.22 (95% confidence interval (CI): 0.11-0.48, P = 0.96). The small number of studies and paucity of multivariate analyses are the limitations of our study. Conclusions: This is the first rigorous pooled analysis assessing ATRX/DAXX mutation as prognostic biomarkers in PanNETs. Patients with altered ATRX/DAXX gene would have poor DFS according to the combined data. And altered ATRX/DAXX genes in metastatic patients showed a trend towards improved overall survival, although the difference did not reach statistical significance.